Ouvrier’s Modified Mini Mental State Examination as a screening test for cognitive impairment in school-aged children with epilepsy - Hariadi Edi Saputra; Setyo Handryastuti; Irawan Mangunatmadja; Dwi Putro Widodo; Sudung O. Pardede (Indonesian Pediatric Society, 2020)
Background Epilepsy may affect children's development, including their cognitive function. The prevalence of cognitive impairment in epilepsy patients is quite high. Weschler Intelligence Scale for Children (WISC) takes a long time to administer and is expensive, so a simpler screening tool for cognitive evaluation is needed in pediatric epilepsy patients. Objective To assess the diagnostic value of Ouvrier’s Modified Mini Mental State Examination (MMSE) for detecting cognitive impairment in children aged 8-11 years with epilepsy. Methods This diagnostic study was conducted in December 2018 to February 2019 at Cipto Mangunkusumo and Fatmawati Hospitals in Jakarta. Data were collected with purposive sampling of children with epilepsy aged 8 to 11 years. Cognitive function was assessed by Ouvrier’s Modified MMSE and WISC. Ouvrier’s Modified MMSE was compared to WISC as and the gold standard. Results were analyzed using a 2x2 table. Results The prevalence of cognitive impairment in 8-11-year-old epilepsy patients was 72.9%. Ouvrier’s Modified MMSE had 83% sensitivity, 85% specificity, 94% positive predictive value, 65% negative predictive value, and 83% accuracy. Conclusions Ouvrier’s Modified MMSE has good diagnostic value, thus it may be useful for early detection of cognitive impairment in pediatric epilepsy.